Work Schedules - Jed DeVaro (Institute of Labor Economics (IZA), 2024)
In a new model of work schedules, employers choose the number of working hours and either dictate the exact hours to be worked or delegate that decision to workers via flextime. Workers' preferences over schedules influence their productivities. An inverted-U-shaped hours-output profile arises; flextime policies shift its peak to the right. Long hours are found to go hand-in-hand with flextime, and the employer finds flextime less appealing when wages exogenously increase. Analysis of a worker-employer matched panel of British workplaces surveyed in 2004 and 2011 reveals that flextime and other flexible work practices mitigate the productivity-eroding consequences of long hours.
Keywords: J20; J23; J24; J32; M52; M50; M59; 330; work hours; labor productivity; human resources management practices; flextime; work-life flexibility; workplace flexibility; work schedules; scheduling; working from home; flexible work practices; diminishing returns